2020
DOI: 10.26443/mjm.v10i1.462
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Clinical Outcome of a Porous Tantalum Implant for the Treatment of Advanced Osteonecrosis of the Femoral Head

Abstract: Purpose of the study: Osteonecrosis of the hip mostly affects young individuals and oftenprogresses to a debilitating disease. Several treatment modalities exist, but none are completely satisfactory. This study evaluates the clinical outcome of patients treated with core decompression and insertion of a porous tantalum implant in the femoral head. This procedure is similar to commonly performed procedures, but has the additional advantages of providing structural support to the necrotic femoral head while hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…This method was first proposed by Brown et al in 1993 (6) who indicated that a porous tantalum rod was a reasonable mechanical substitute for a fibular graft. In a multicenter study, Tsao et (22). Although there was no statistical difference between Runze and Zimmer implants in our study, the survival rate was significantly higher than that reported in Tsao et al (5), Liu et al (20), and Nadeau et al (22), and similar to that of Pakos et al (19).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This method was first proposed by Brown et al in 1993 (6) who indicated that a porous tantalum rod was a reasonable mechanical substitute for a fibular graft. In a multicenter study, Tsao et (22). Although there was no statistical difference between Runze and Zimmer implants in our study, the survival rate was significantly higher than that reported in Tsao et al (5), Liu et al (20), and Nadeau et al (22), and similar to that of Pakos et al (19).…”
Section: Discussionsupporting
confidence: 79%
“…In a multicenter study, Tsao et (22). Although there was no statistical difference between Runze and Zimmer implants in our study, the survival rate was significantly higher than that reported in Tsao et al (5), Liu et al (20), and Nadeau et al (22), and similar to that of Pakos et al (19). Thus, Runze tantalum implants, with a 95% survival, appear to be a feasible option.…”
Section: Discussionsupporting
confidence: 73%
“…However, the long-stage effect of porous tantalum rod implantation is uncertain. Porous tantalum rod implantation in the treatment of femoral head necrosis failed and convert to THA has been successively reported [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…ONFH is a progressive disease that easily affects young patients with age about 35 years [ 24 ].The young patients have a good prognosis after hip conserving surgery. The follow-up results of Nadeau et al [ 18 ] showed that the mean age at surgery of the patients who failed was (50.1 ± 12.1) years old, compared to a mean age of (36.8 ± 12.2) years old for the patients whose tantalum implant did not fail, with significant difference ( P < 0.05). Age is one of the prognostic factors of porous tantalum rod implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Long, et al [99] and Meneghini, et al [100] implanted porous TA seal cones into patients with total knee arthroplasty and found them to have stable bone ingrowth and good osseo-integration. Nadeau, M. et al [101] reported overall 44.5% success rate when porous TA plugs were implanted into 15 patients with advanced stage of osteonecrotic hips. Tsao, et al [102] conducted a similar study where porous TA plugs were implanted into 98 patients with early-stage osteonecrotic hips and found that the average Harris hip score increased from 63 preoperatively to 83 after 4 years.…”
Section: Tantalummentioning
confidence: 99%